THEORETICAL PRINCIPLES OF THE FORMATION OF NATIONAL SOLIDARITY AMONG SCHOOLCHILDREN AND STUDENT YOUTH IN WAR AND POST-WAR TIMES - Zhurba, Kateryna; Shkilna, Iryna (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The article highlights the theoretical principles of the formation of national solidarity among schoolchildren and student youth in the conditions of war and post-war times. In order to solve the research tasks, the following methods were used: analysis and synthesis of psychological and pedagogical sources, comparison, classification, systematization and generalization of theoretical principles, substantiation and development of the content of the formation of the structure of national solidarity among schoolchildren and student youth. A categorical research apparatus has been developed and the concepts of “solidarism”, “national solidarity”, “national identity”, “civic competence”, “civic resilience” were defined. It has been proven that national solidarity is the most important moral characteristic of the Ukrainian national community, which determines the national kinship of members of Ukrainian society through a system of values, national consciousness, national culture, language, manifested in self-organization, active citizenship, the ability to act for a common goal and common good. Internal national solidarity (as a commonality of actions and their coordination in the face of various challenges of people of different social, ethnic groups, generations (parents and children) for the achievement of a common goal, common good) and transnational solidarity (as the ability not only of Ukrainians but also of entire countries) are singled out. The stages of formation of national solidarity are determined: family, tribal, tribal, national identity. A four-component content structure of the formation of national solidarity among schoolchildren and student youth, containing cognitive, emotional-valuable, arbitrary motivation and behavioral components, is singled out. The practical significance of the article is that its materials can be used in studying the specified problem and in organizing educational work in institutions of general secondary education, institutions of higher education, and training of teachers.